INFLUÊNCIA DA TEMPERATURA DA ÁGUA DE CULTIVO NO DESEMPENHO ZOOTÉCNICO DE PIAU CORRÓ (LEPORINUS LACUSTRIS) - MACHADO, João Victor Bezerra1, (joaovictorbezerramachado@gmail.com; NETO, Nilton de Magalhães; ACUNHA, Rubia Mara Gomes; WANDERLEY,Alysson Martins; COSTA, Deliane Cristina; CAMPOS, Cristiane Meldau de (ANAIS DO ENIC, 2023)
-